Complement in therapy and disease: Regulating the complement system with antibody-based therapeutics. Issue 2 (October 2015) - Melis, Joost P.M.; Strumane, Kristin; Ruuls, Sigrid R.; Beurskens, Frank J.; Schuurman, Janine; Parren, Paul W.H.I.
Highlights: The complement cascade: a fine molecular interplay regulates functional outcome. An imbalance by overactive or attenuated complement activation has severe pathological implications. Enhancement or inhibition of complement creates a powerful strategy for therapeutic intervention. Synergy between complement and cell-mediated effector functions impacts therapeutic efficacy. Antibody combination therapies, engineering approaches and optimized treatment designs provide exciting opportunities for new and improved therapies. Abstract: Complement is recognized as a key player in a wide range of normal as well as disease-related immune, developmental and homeostatic processes. Knowledge of complement components, structures, interactions, and cross-talk with other biological systems continues to grow and this leads to novel treatments for cancer, infectious, autoimmune- or age-related diseases as well as for preventing transplantation rejection. Antibodies are superbly suited to be developed into therapeutics with appropriate complement stimulatory or inhibitory activity. Here we review the design, development and future of antibody-based drugs that enhance or dampen the complement system.